Tinjauan Literatur Kepemimpinan Transformasional pada Usaha Kecil Menengah (UKM) - Lazuardi, Muhammad Lutfi; Rizal, Muhammad; Arifianti, Ria (Organum: Jurnal Saintifik Manajemen dan Akuntansi, 2018)
Transformational leadership is a leadership style. The leader, capable of identifying the changes that need to be made, creating a vision to guide the changes through inspiration and implementing them under group commitment. The role of a leader in exerting his/her influences is so important for supporting the company activities, including Small and Medium Enterprises (SMEs). A comprehensive understanding of the state-of-the-art of transformational leadership is still needed. Therefore, this article aims to classify, identify scientific publications and carry out a thematic analysis of the latest literature to create an extensive and detailed understanding of transformational leadership specifically in Small and Medium Enterprises (SMEs). The research method was conducted by using Systematic Mapping Study (SMS) to analyze scientific publications of transformational leadership in Small and Medium Enterprises (SMEs) which were generated based on the focus and type of research from time to time. The results of this study produced a categorization and quantification of transformational leadership studies in various dimensions as well as an overview of topics and trends in transformational leadership research in Small and Medium Enterprises (SMEs) today.